2016
DOI: 10.17569/tojqi.229494
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Members’ Point of Views Regarding Lifelong Learning

Abstract: ÖzBu çalışmanın amacı, öğretim elemanlarının yaşamboyu öğrenmeye yönelik düşüncelerini ve yaşamboyu öğrenme özelliklerini etkileyen faktörleri ortaya koymaktır. Bu amaç doğrultusunda söz konusu araştırma olgu bilim deseni ile desenlenmiştir. Araştırmanın

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…It has been observed that pre-service teachers' responses to the necessity of Adult Education and Lifelong Learning were mainly based on individual, social, and professional development. This result is consistent with the literature (Günüç, Odabaşı & Kuzu, 2012;Haseski & Odabaşı, 2016;Jarvis, 2007;Kurt, 2000;Laal, 2013;Tan & Morris, 2006). This result is in line with the idea that lifelong learning and adult education contribute to different development areas (Dinevski & Dinevski, 2004;Merriam & Brockett, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…It has been observed that pre-service teachers' responses to the necessity of Adult Education and Lifelong Learning were mainly based on individual, social, and professional development. This result is consistent with the literature (Günüç, Odabaşı & Kuzu, 2012;Haseski & Odabaşı, 2016;Jarvis, 2007;Kurt, 2000;Laal, 2013;Tan & Morris, 2006). This result is in line with the idea that lifelong learning and adult education contribute to different development areas (Dinevski & Dinevski, 2004;Merriam & Brockett, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…This reinforces lifelong learning opportunities for teachers. Previous research on faculty members' opinions of the effects of technology on lifelong learning also supports this (Haseski & Odabaşı, 2016). In the words of one research participant, "[i]nformation and communication technologies encourage active participation in lifelong learning since they facilitate access to information and render this process interesting" (Haseski & Odabaşı, 2016, p. 345).…”
mentioning
confidence: 77%
“…Likewise, Selvi (2011) identified the ability to benefit from in-service teacher training opportunities and participation in seminars and conferences, as well as engagement in research as key lifelong learning skills. Haseski and Odabaşı (2016) also found that faculty members believe professional development activities significantly enhance their lifelong learning skills. Similarly, in another study it was found that teachers' participation in professional development activities enhanced their skills in technology use and communication with parents as well as colleagues, hence creating further motivation for engaging in lifelong learning (Erdem & Koç, 2016).…”
mentioning
confidence: 92%
See 1 more Smart Citation